Myeloid-Derived Suppressor Cells as Therapeutic Target in Hematological Malignancies - De Veirman, Kim; Van Valckenborgh, Els; Lahmar, Qods; Geeraerts, Xenia; De Bruyne, Elke; Menu, Eline; Van Riet, Ivan; Vanderkerken, Karin; Van Ginderachter, Jo A. (Frontiers in Oncology, 2014)
Myeloid derived suppressor cells (MDSC) are a heterogeneous population of immature myeloid cells that accumulate during pathological conditions such as cancer and are associated with a poor clinical outcome. MDSC expansion hampers the host anti-tumor immune response by inhibition of T cell proliferation, cytokine secretion and recruitment of regulatory T cells. In addition, MDSC exert non-immunological functions including the promotion of angiogenesis, tumor invasion and metastasis. Recent years, MDSC are considered as a potential target in solid tumors and hematological malignancies to enhance the effects of currently used immune modulating agents. This review focuses on the characteristics, distribution, functions, cell-cell interactions and targeting of MDSC in hematological malignancies including multiple myeloma, lymphoma and leukemia.